2007
DOI: 10.1007/s11373-007-9176-0
|View full text |Cite
|
Sign up to set email alerts
|

Tying SUMO modifications to dynamic behaviors of chromosomes during meiotic prophase of Saccharomyces cerevisiae

Abstract: In budding yeast Saccharomyces cerevisiae, centromeres and telomeres are tethered to the nuclear envelope during premeiotic interphase. Immediately after cells enter meiotic prophase, chromosomes undergo global reorganization, including bouquet formation (telomere clustering), non-homologous centromere coupling, homologous pairing, and assembly/disassembly of synaptonemal complexes. These chromosome dynamics have been implicated in promoting pairing, synapsis, crossover DNA recombination and segregation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…These, as well as Smt3 aggregates, colocalized with Zip1 in the ipl1-mn mutant (Fig. 5H), consistent with the model that Smt3 is a substrate of Zip1 (Cheng et al 2007). …”
Section: Dissociation Of Central and Lateral Element Components Are Dsupporting
confidence: 86%
“…These, as well as Smt3 aggregates, colocalized with Zip1 in the ipl1-mn mutant (Fig. 5H), consistent with the model that Smt3 is a substrate of Zip1 (Cheng et al 2007). …”
Section: Dissociation Of Central and Lateral Element Components Are Dsupporting
confidence: 86%
“…Therefore, it is possible that Rec10 is only non-covalently bound by SUMO, and other LinE proteins, such as Rec25 and Rec27, are SUMO targets. Also, Pds5 is a possible candidate as it localizes to meiotic chromosome axes (Ding et al 2006) and was shown to be a SUMO target in the budding yeast (see Cheng et al 2007). Rec10 modification then may occur in response to the SUMOylation of one of its interacting partners.…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomyces cerevisiae Zip1 and related proteins of other organisms are the main components of the transversal filaments (see Zickler and Kleckner 1999). In S. cerevisiae, it was found that Zip1 polymerizes along the axial elements concomitantly with their modification by the small ubiquitin-like modifier (SUMO) (see Cheng et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence indicate that protein modification by the ubiquitin-related protein SUMO plays a role in meiosis (28)(29)(30)(31)(32)(33)(34). In particular, the SC itself seems to contain SUMO because the SC can be stained with SUMOspecific antibodies along its entire axis (28).…”
Section: -1-1-red1 Interaction Is Essential For Meiotic Checkpoint Smentioning
confidence: 99%